Risk indicators for aggressive periodontitis in an untreated isolated young population from Brazil - Priscila Corraini; Cláudio Mendes Pannuti; Alessandro Nautili Pustiglioni; Giuseppe Alexandre Romito; Francisco Emílio Pustiglioni (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This study aimed to assess the prevalence of aggressive periodontitis (AgP), and to investigate the association between demographic, socioeconomic and behavioral risk indicators with AgP in an untreated and isolated young population in Southeastern Brazil. For this cross-sectional survey, 134 subjects aged 12-29 years were selected by a census. Of those eligible, 101 subjects received a full-mouth clinical examination, and were interviewed using a structured written questionnaire. Cases were defined as individuals with 4 or more teeth with attachment loss > 4 mm or > 5 mm in the age groups 12-19 and 20-29, respectively. Overall, 9.9% of the subjects presented AgP (10.3% of the 12-19-year-olds and 9.7% of the 20-29-year-olds). The only risk indicator significantly associated with AgP in this isolated population was a high proportion of sites (> 30%) presenting supragingival calculus [OR = 23.2]. Having experienced an urgency dental treatment was a protective factor for AgP [OR = 0.1]. The authors concluded that this isolated and untreated population from Brazil presented a high prevalence of AgP. Local plaque-retaining factors played a major role in the prevalence of AgP in this isolated population, and should be included in further studies evaluating this destructive periodontal disease form.